Leveraging Social Media Marketing for Brand Growth: Evidence from Glad2Glow Skincare - Juanita, Nayla; Aryani, Nova; Wulandari, Eliyana; Salsabila, Sandrella; Khadifa Abdul Rozzaq Wijaya, Rahmaditya (LPPM Universitas Duta Bangsa Surakarta, 2025)
The advancement of digital technology has positioned social media as a vital tool for marketing and competitive advantage. This study examines how social media marketing (SMM) strategies enhance brand growth through a qualitative descriptive approach and literature review, focusing on the case of Glad2Glow Skincare on Instagram. Data were drawn from scholarly articles, industry reports, and analysis of influencer promotional content. The findings reveal that content type and message framing significantly impact engagement. For instance, Aqeela Calista’s reel generated 229,000 likes, 1,041 comments, and 1,785 shares, making it the most effective in driving interaction. Similarly, Syifa Hadju’s testimonial-style feed post gained 78,500 likes and 522 comments, showing the power of authenticity in building trust. In contrast, static feed posts such as Amanda Manopo’s (19,900 likes; 440 comments) and Elina Joerg’s (16,500 likes; 294 comments) attracted lower engagement, highlighting the superiority of reels and short-video formats. These results align with prior studies emphasizing emotional appeal and interactive strategies as key drivers of consumer participation. Nevertheless, challenges such as algorithm changes and sustaining long-term loyalty persist. The case of Glad2Glow demonstrates that strategic influencer collaborations, dynamic content design, and consumer-centric engagement can transform social media into a powerful driver of competitive advantage in the beauty industry.